(Proper) practice helps: Results of a multicentre trial of Deliberate Practice for the acquisition of basic therapeutic skills - Barke, Antonia; Doering, Bettina; Forkmann, Thomas; Ruhleder, Mirjana; Weise, Cornelia; Korwisi, Beatrice (EACLIPT Conference 2025, 2025)
Introduction: Deliberate Practice (DP) is a structured method for the acquisition of complex skills that is used in the training of musical and athletic performance. Recently, DP has been applied to psychotherapy training; however, data on its effectiveness and acceptance among students are sparse. Methods: Students of the clinical master's programme at three universities (Erlangen, Essen, Kiel) completed the German version of the Counselor Activity Self-Efficacy Scale (CASES-R) before (baseline) and after (post) 11 hours of teaching basic psychotherapy skills using DP. At both time points, the students also recorded a five-minute interaction sequence with an actor simulating a standardized patient, which were rated by external supervisors (blind to the time of recording) regarding a set of competencies. The students also answered questions about their acceptance of DP. Result: Pilot data from Essen are currently available. At the time of the conference, we will report on the multicentre data. In the pilot data (n=17), there was an increase in therapeutic self-efficacy (d=1.0) and improvements in the external assessments (d=0.53 to d=0.90). The acceptance of DP was high (8.7±0.7). The structured feedback process was perceived as helpful [8.9±0.3] and hardly any unpleasant feelings were reported. The expert-rated improvements correlated exclusively with the time spent practicing independently with the video prompts between sessions (r =.45, p<.05). Conclusion: Initial pilot data show that DP is well received by students and leads to improvements in therapeutic self-efficacy and peer-rated skills. Personal practice with provided video prompts correlates with improvements in performan